Pelatihan Menulis Aksara Jawa: Meningkatkan Kemampuan Menulis dan Melestarikan Budaya Jawa - Wijayanto, Catur Sunu; Nurcahyawati, Enny; Nugraha, Renanda Adhi (Neolectura, 2024)
The Javanese script is one of the most important cultural heritages of Java that needs to be preserved. However, the ability to write in Javanese script is fading among the Javanese community. Therefore, training in writing Javanese script is urgently needed to improve writing skills and preserve Javanese culture. This article discusses the training in writing Javanese script that has been conducted and its results. The Javanese script is one of the most important cultural heritages of Java that needs to be preserved. However, the ability to write in Javanese script is fading among the Javanese community. Therefore, training in writing Javanese script is urgently needed to improve writing skills and preserve Javanese culture. This research aims to develop and test the effectiveness of training in writing Javanese script. The research method used is action research with a classroom action research design. The results show that training in writing Javanese script can improve students' ability to write in Javanese script. In addition, this training can also increase students' awareness and appreciation of Javanese culture and the importance of preserving the Javanese script. Therefore, training in writing Javanese script is crucial for preserving and developing Javanese culture